2022
DOI: 10.3389/fcimb.2022.984140
|View full text |Cite
|
Sign up to set email alerts
|

Rapid detection of Burkholderia cepacia complex carrying the 16S rRNA gene in clinical specimens by recombinase-aided amplification

Abstract: The Burkholderia cepacia complex (BCC) is a group of opportunistic pathogens, including Burkholderia cepacia, Burkholderia multivorans, Burkholderia vietnamiensis and Burkholderia ambifaria, which can cause severe respiratory tract infections and lead to high mortality rates among humans. The early diagnosis and effective treatment of BCC infection are therefore crucial. In this study, a novel and rapid recombinase-aided amplification (RAA) assay targeting the 16S rRNA gene was developed for BCC detection. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Compared with the general molecular detection methods, RAA possesses several advantages, such as low-cost, simplicity of operation (as it does not necessitate complex equipment or highly skilled personnel, can be conducted using portable device), low and constant reaction temperature (39°C), and rapid reaction speed (within 20 min) ( Xie et al., 2012 ). As a result, RAA has been widely used in identifying viruses, bacteria, and parasites ( Cui et al., 2022 ; Fu et al., 2022 ; Lin et al., 2022 ; Cui H et al., 2023 ; Cui X et al., 2023 ). Consequently, it represents a rapid and user-friendly method suitable for clinical use, particularly in primary laboratories.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with the general molecular detection methods, RAA possesses several advantages, such as low-cost, simplicity of operation (as it does not necessitate complex equipment or highly skilled personnel, can be conducted using portable device), low and constant reaction temperature (39°C), and rapid reaction speed (within 20 min) ( Xie et al., 2012 ). As a result, RAA has been widely used in identifying viruses, bacteria, and parasites ( Cui et al., 2022 ; Fu et al., 2022 ; Lin et al., 2022 ; Cui H et al., 2023 ; Cui X et al., 2023 ). Consequently, it represents a rapid and user-friendly method suitable for clinical use, particularly in primary laboratories.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on viral and bacterial pathogens have indicated the detection limit of the RAA assay varied from 10 to 142 copies per reaction when tested against standard plasmids ( Zhang et al., 2017 ; Cui et al., 2022 ; Fu et al., 2022 ; Lin et al., 2022 ; Cui H et al., 2023 ; Cui X et al., 2023 ). In this study, a novel and simple method for E. piscicida detection was proposed based on RAA technique.…”
Section: Discussionmentioning
confidence: 99%
“…This was contrary to a study by Patra et al in 2014 in which susceptibility to Meropenem was 100%, followed by Ceftazidime-sulbactam and Pipera-cillin Tazobactam. 17 Another study in Bangladesh showed 100% sensitivity to Meropenem, and 93% of isolates were resistant or intermediate to levofloxacin. 19 The results from SENTRY Antimicrobial surveillance program showed greater than 90% susceptibility to Minocycline, similar to our results in which Minocycline is considered the most effective antibiotic.…”
Section: B Cepacia Was Isolated From Clinical Samples Of 419mentioning
confidence: 99%
“…A study published in the Annals of Tropical Medicine and Health showed that the prevalence of Burkholderia cepacia was highest from blood cultures. 17 A study in China showed that respiratory specimens were on top. 18 Our study demonstrated that Minocycline was the least resistant antimicrobial agent, followed by Cotrimoxazole 6.2%, Chloramphenicol 7.15% and Levofloxacin 11%.…”
Section: B Cepacia Was Isolated From Clinical Samples Of 419mentioning
confidence: 99%
“…RPA can amplify targets up to 1.5 kb but is better suited to amplicons between 100 and 200 bp, with an optimal amplification time of 20 min [ 9 , 11 , 13 ]. Recently, RPA has successfully targeted Burkholderia spp., including Burkholderia pseudomallei [ 14 , 15 , 16 ], Burkholderia mallei [ 17 ], and BCC [ 18 ]. More recently, Fu et al [ 18 ] reported a recombinase-aided amplification (RAA) targeting the 16S rRNA gene for BCC detection.…”
Section: Introductionmentioning
confidence: 99%